87.5k views
2 votes
Consider the equation below.

5(3a−1)−2(3a+2)=3(a+2)+v
Select two expressions that are equivalent to v.

2 Answers

4 votes
Wronggg what they told you was wrong
User Greggannicott
by
5.4k points
4 votes

Answer:

Its option C. 6a-7

Step-by-step explanation:

Given that 5(3a-1)-2(3a-2)=3(a+2)+v . You solve for v by:

v = 5(3a-1)-2(3a-2) - 3(a+2)

v = 15a - 5 - 6a + 4 - 3a - 6

v = 15a - 6a - 3a - 5 + 4 - 6

v = 6a - 7

So the answer is option C. 6a-7

User William Gu
by
5.9k points